2013
DOI: 10.1097/ccm.0b013e31828c26b5
|View full text |Cite
|
Sign up to set email alerts
|

Enterocyte Damage in Critically Ill Patients Is Associated With Shock Condition and 28-Day Mortality*

Abstract: In critically ill patients, enterocyte damage is frequent, and it is significantly associated with shock and 28-day mortality. The link between intestinal fatty acid-binding protein and plasma citrulline concentrations in critically ill patients needs to be further evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 23 publications
5
58
2
1
Order By: Relevance
“…Surprisingly, we were not able to confirm results from other literature, which found that elevated iFABP correlates with both greater enterocyte damage and elevated lactate levels (12,13). Although MAP and Hb are independently associated with increased iFABP levels (13), these parameters cannot explain any differences as they did not vary between the trauma groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, we were not able to confirm results from other literature, which found that elevated iFABP correlates with both greater enterocyte damage and elevated lactate levels (12,13). Although MAP and Hb are independently associated with increased iFABP levels (13), these parameters cannot explain any differences as they did not vary between the trauma groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Plasma citrulline and Òintestinal Fatty Acid Binding ProteinÓ (iFABP) have been suggested as reliable biomarkers for assessing gut injury (8)(9)(10)(11)(12)(13)(14). Citrulline is an amino acid synthesized in small bowel enterocytes from glutamine and is constantly released to the blood (8).…”
Section: Introductionmentioning
confidence: 99%
“…Citrulline is an amino acid mainly synthesized by small bowel enterocyte, and the concentration of plasma citrulline has previously been recognized as a marker of functional enterocyte mass in small bowel diseases (7)(8)(9). In addition, low plasma citrulline concentrations in critically ill patients are associated with a high mortality rate (10,11). Intestinal fatty acid-binding protein (I-FABP), a protein specifically localized in small bowel enterocytes, is released in plasma in case of enterocyte damage (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on citrulline have focused only on diseases such as short bowel syndrome [5], viral enteritis [4], intestinal transplants [6], intestinal toxicity due to chemotherapy [7], and Crohn's disease [8]. More recently, there have been a few studies that have focused on critically ill patients [9,10]. Crenn et al showed that plasma citrulline levels decreased, and were lower when digestive bacterial translocation occurred at the onset of septic shock.…”
Section: Introductionmentioning
confidence: 99%